2021
DOI: 10.3390/biom11081238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiovascular Risk in Women with Periodontal Diseases According to C-reactive Protein Levels

Abstract: Cardiovascular diseases (CVD) are highly prevalent non-communicable diseases worldwide. Periodontitis may act as a non-traditional cardiovascular risk (CVR) factor, linked by a low-grade systemic inflammation mediated by C-reactive protein (CRP). Patients with periodontitis reported higher serum CRP levels; however, a CRP systemic and periodontal correlation in gingival crevicular fluid (GCF) and its CVR impact have been barely studied. We aimed to assess the association between periodontal diseases and CVR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…7,8 Furthermore, local periodontal inflammation has been associated with major adverse cardiovascular events through a mechanism of increased arterial inflammation. 9 Therefore, CRP levels have been suggested as one of the tools to assess the risk of cardiovascular disease due to periodontitis, 10 since CRP serum levels are elevated in patients with periodontal disease. 11,12 A metaanalysis investigating the relation of CRP with periodontitis have shown that CRP in patients with periodontitis of different severity is elevated compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Furthermore, local periodontal inflammation has been associated with major adverse cardiovascular events through a mechanism of increased arterial inflammation. 9 Therefore, CRP levels have been suggested as one of the tools to assess the risk of cardiovascular disease due to periodontitis, 10 since CRP serum levels are elevated in patients with periodontal disease. 11,12 A metaanalysis investigating the relation of CRP with periodontitis have shown that CRP in patients with periodontitis of different severity is elevated compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Crescioli [ 4 ] clearly reviewed the protective role of vitamin D in female cardiac health, discussing that vitamin D controls together with estrogens some intracellular signaling paths [ 5 ], so that the unfavorable association of hypoestrogenism-D hypovitaminosis likely converges towards maladaptive cardiomyocyte remodeling and contributes to increase CVD risk in post-menopause. Da Venezia et al [ 6 ] assessed the association between periodontal diseases and CV risk based on serum high-sensitivity C-reactive protein, plainly showing a link between periodontitis, that might act as a non-traditional CV risk factor, and a low-grade systemic inflammation mediated by C-reactive protein. They showed the systemic and periodontal correlation in women’s gingival crevicular fluid and its impact on CV risk.…”
mentioning
confidence: 99%